PENERAPAN MODEL PEMBELAJARAN PjBL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Mufidah, Anisah; Hadi, Najmul; Muhammad , Farhana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to increase the learning activeness of students by using a project-based learning model (PJBL). This type of research is class action research. Data collection methods are using observation sheets and questionnaires. The subjects of this study were fourth grade students of SDN 02 Tebaban. Fourth grade students totaled 18 people, consisting of 12 male students and 6 female students. The results showed an increase in student learning activeness. The results of observation of students' learning activeness showed that in the pre-cycle the activeness of students was only 52%, then increased to 60% in cycle I, and increased again to 72% in cycle II. Then the results of the learning activeness questionnaire from students also showed a similar increase. In the pre-cycle, the results of the analysis showed that the learning activeness of students was 57%, then increased to 70% in cycle I, and increased again in cycle II to 77%.